ADVANCING EXCELLENT PUBLIC SERVICE IN PALEMBANG CITY: A SYSTEMATIC LITERATURE REVIEW WITH VOSVIEWER ANALYSIS - Putra, Raniasa; Lionardo, Andries; Nur Budiyanto, Muhammad; Nisyak, Hoirun; Syafebri, Arrahman (Indonesian Association for Public Administration (IAPA), 2025)
This study explores the advancement of excellent public service in Palembang City through a Systematic Literature Review (SLR) of 36 articles published between 2020 and 2024. The review employed the PRISMA framework to ensure transparency and rigor, while bibliometric analysis was conducted using VOSviewer 1.6.20 to map thematic structures. The findings reveal four dominant clusters shaping the discourse: (1) digital transformation in public service, (2) citizen trust and satisfaction, (3) bureaucratic reform and service innovation, and (4) participatory governance and collaborative networks. These dimensions highlight that excellent public service is not merely about efficiency, but also requires inclusivity, transparency, and institutional adaptability. This study contributes to the theoretical development of public administration by synthesizing emerging trends in digital and participatory governance, while offering practical implications for local governments in designing responsive and citizen-centered services.